Identification and Characterization of an Early Leaf Senescence Gene ELS1 in Soybean - Yamatani, Hiroshi; Heng, Titnarong; Yamada, Tetsuya; Kusaba, Makoto; Kaga, Akito (Frontiers in Plant Science, 2021)
Early leaf senescence phenotype in soybean could be helpful to shorten the maturation period and prevent green stem disorder. From a high-density mutation library, we identified two early leaf senescence soybean mutant lines, els1-1 (early leaf senescence 1) and els1-2. The chlorophyll contents of both els1-1 and els1-2 were low in pre-senescent leaves. They degraded rapidly in senescent leaves, revealing that ELS1 is involved in chlorophyll biosynthesis during leaf development and chlorophyll degradation during leaf senescence. The causal mutations in els1 were identified by next-generation sequencing-based bulked segregant analysis. ELS1 encodes the ortholog of the Arabidopsis CaaX-like protease BCM1, which is localized in chloroplasts. Soybean ELS1 was highly expressed in green tissue, especially in mature leaves. The accumulation of photosystem I core proteins and light-harvesting proteins in els1 was low even in pre-senescent leaves, and their degradation was accelerated during leaf senescence. These results suggest that soybean ELS1 is involved in both chlorophyll synthesis and degradation, consistent with the findings in Arabidopsis BCM1. The gene els1, characterized by early leaf senescence and subsequent early maturation, does not affect the flowering time. Hence, the early leaf senescence trait regulated by els1 helps shorten the harvesting period because of early maturation characteristics. The els1-1 allele with weakly impaired function of ELS1 has only a small effect on agricultural traits and could contribute to practical breeding.